Conspicuous Consumption in the United States and China - David Jinkins (Institute for the Study of Labor (IZA), 2014)
I develop a model of conspicuous consumption to empirically measure the importance of peer beliefs to Americans and Chinese. In the model, a consumer cares not only about the direct utility she receives from consumption, but also about the way her consumption pattern affects her peer group's belief about her well-being. I estimate the model on household budget surveys. According to model estimates, a Chinese consumer cares 20% more than an American consumer about peer beliefs. The absolute size of the conspicuous consumption motive in both countries is relatively small. I use the estimated model to evaluate the welfare effect of the 1990-2002 American luxury tax on automobiles. The luxury tax benefited nearly all Americans a small amount, but hurt the small fraction of consumers who love automobiles the most.
Keywords: D12; 330; behavioral economics; conspicuous consumption; applied microeconomics